Genetic profiles of Schistosoma haematobium parasites from Malian transmission hotspot areas - IBIKOUNLE, MOUDACHIROU (My University, 2023)
Abstract Background Although schistosomiasis is a public health issue in Mali, little is known about the parasite genetic profile. The purpose of this study was to analyze the genetic profile of the schistosomes of Schistosoma haematobium group in school-aged children in various sites in Mali. Methods Urine samples were collected from 7 to 21 November 2021 and subjected to a filtration method for the presence S. haematobium eggs. The study took place in two schistosomiasis endemic villages (Fangouné Bamanan and Diakalèl), qualified as hotspots according to the World Health Organization (WHO) definition. Molecular genotyping on both Cox1 and ITS2/18S was used for eggs’ taxonomic assignation. Results A total of 970 miracidia were individually collected from 63 school-aged children and stored on Whatman FTA cards for molecular analysis. After genotyping 42.0% (353/840) and 58.0% (487/840) of miracidia revealed Schistosoma bovis and S. haematobium Cox1 profiles, respectively; 95.7 (885/925) and 4.3% (40/925) revealed S. haematobium and S. haematobium/S. curassoni profiles for ITS/18S genes, respectively. There was a significant difference in the Cox1 and ITS2/18S profile distribution according to the village (P < 0.0001). Overall, 45.6% (360/789) were ybrids, of which 72.0% (322/447) were from Diakalèl. Three hybrids’ profiles (Sb/Sc_ShxSc with 2.3%; Sb/Sc_ShxSh with 40.5%; Sh_ShxSc with 2.8%) and one pure profile (Sh_ShxSh with 54.4%) were identified. Conclusion Our findings show, for the first time to our knowledge, high prevalence of hybrid schistosomes in Mali. More studies are needed on population genetics of schistosomes at the human and animal interface to evaluate the parasite’s gene flow and its consequences on epidemiology of the disease as well as the transmission to humans.
Keywords: Schistosoma haematobium; Schistosoma bovis; Schistosoma curassoni; Hybridization; Cox1; ITS/18S; Mali